The effect of augmented reality-based Snake and Ladder game on early childhood cognitive development - Nugroho, Dicky Anggriawan; Zubaidi, Muhammad Fikri bin; Winasari Winasari (Jurnal Inovasi Teknologi Pendidikan, 2025)
This study examines the impact of an Augmented Reality (AR)-based Snake and Ladder board game on improving early childhood cognitive abilities. Conventional learning often causes boredom and limits children’s creativity, so innovative media that stimulate reasoning and imagination are needed. Using the Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), this research involved 26 children at Bustanul Athfal Sragi Kindergarten. The analysis phase revealed that children were active, competitive, and curious. The AR-based Snake and Ladder game was designed by integrating physical boards with AR question cards connected to 3D objects in the Assemblr EDU application. Media and material experts validated the product with feasibility scores of 84% and 80%, both categorized as “Highly Valid.” Implementation results showed that the AR-based game effectively increased children’s interest, enthusiasm, curiosity, and cognitive stimulation through an engaging blend of digital and real-world interaction, aligning with the “learning while playing” principle and fostering early technological literacy. Further research is recommended to explore similar technology-based learning media across different educational contexts, age groups, and subjects to enhance understanding of its effectiveness and long-term educational benefits.